Unlocking Sustainable Firm Performance: The Influence of Sustainability Reporting, Green Accounting, and Intellectual Capital - Fadhila Azzahra; Vita Citra Mulyandini (LP2M IAIN Palopo, 2025)
Companies play an important role in driving national economic growth, however, their operational activities may also pose environmental risks. This study aims to examine the influence of sustainability reporting, green accounting, and intellectual capital on the performance of basic materials companies listed on the IDX during 2021–2024. A quantitative approach was employed using secondary data obtained from annual and sustainability reports. From a population of 110 companies, 16 firms were selected through purposive sampling. The data were analyzed using multiple linear regression with IBM SPSS 31. The results show that sustainability reporting, Value Added Capital Employed (VACA), and Value Added Human Capital (VAHU) exert a positive and significant influence on firm performance, while green accounting and Structural Capital Value Added (STVA) have no significant influence. Furthermore, the three independent variables simultaneously have a positive and significant effect on firm performance. These findings suggest that enhancing the quality of sustainability disclosures and optimizing intellectual capital, particularly financial and human resources, may strengthen firm performance.